(untitled) (International Journal of Engineering and Computer Science, 2018)
Character segmentation is a vital area of research for optical character recognition. The process of OCR involves several steps to recognize the character. After converting the scanner’s output as bitmap image, set its threshold value. The recognition phase’s output is totally depends upon the segmentation phase. Touching and broken character affects the accuracy rate of the recognition phase badly. Existing methods concentrate only upon the single touching characters problem with fixed size and mostly works upon the middle zone. Segmentation of the broken character is an uphill task. In this paper, we used proposed technique for identification and segmentation of multiple touching characters in handwritten Gurmukhi words. In proposed technique firstly scanner’s output is saved as bitmap image and then set its threshold value 200. The bitmap image is segmented into individual characters, called segments after applying the dynamically projection technique. The name of developed method i.e. Dynamic profile projection technique means that it works for variable size. Thus, the new technique works upon the segmentation of broken, multiple touching characters of variable size including the three zones of the handwritten gurmukhi script and increase the accuracy for touching characters. Thus, after the implementation of this concept got encouraging results than the existing systems.